Gaps present a trade‐off between dispersal and establishment that nourishes species diversity. Issue 5 (9th March 2020) - Terborgh, John; Huanca Nuñez, Nohemi; Feeley, Kenneth; Beck, Harald
Abstract: We took advantage of two natural experiments to investigate processes that regulate tree recruitment in gaps. In the first, we examined the recruitment of small and large saplings and trees into 31 gaps resulting from treefalls occurring between 1984 and 2015 in the 2.25‐ha core area of a 4‐ha tree plot at Cocha Cashu in Perú. In the second, we identified the tallest saplings recruiting into 69 gaps created during a violent wind storm in February 2000. In the established tree plot, we were able to compare the composition of saplings in the disturbance zones of gaps prior to, during, and subsequent to the period of gap formation. Recruitment in gaps was compared with that in "nofall" zones, areas within the plot that had not experienced a treefall at least since the early 1980s. Our results confirmed earlier findings that a consistently high proportion ( 60%) of established saplings survived gap formation. Light demanding species, as proxied by mortality rates, recruited under all conditions, but preferentially during periods of gap formation, a pattern that was especially strong among gap pioneers. Similar results were noted, separately, for small and large saplings and trees recruiting at ≥10 cm dbh. One hundred percent of previously untagged trees recruiting into gaps in the first post‐disturbance census were gap pioneers, suggesting rapid development. This conclusion was strongly supported in a follow‐up survey taken of 69 gaps 19 months after they had been synchronously created in a wind storm. Ten species of gap pioneers, eight of which are not normally present in the advance regeneration, had attained heights of 6–10 m in 19 months. The 10 gap pioneers were dispersed, variously, by primates, bats, birds, and wind and reached maximum frequency in different‐sized gaps (range <100 m 2 to >1, 000 m 2 ). Both gap size and limited dispersal of zoochorous species into gaps serve as filters for establishment, creating a complex mosaic of conditions that enhances species diversity.